Multi-axial strain mapping to characterise structure and material properties of the human hip capsule - Kabelan J. Karunaseelan; K.C. Geoffrey Ng; Sarah K. Muirhead-Allwood; Richard J. van Arkel; Jonathan R. T. Jeffers (PLoS ONE, 2026)
The biological composition and spatial arrangement of the tissue’s constituents are directly related to its condition and function. Conventional inspection techniques such as optical microscopy and exogenous staining have limited ability to capture the heterogeneity and anisotropy of biological tissues. Here, we apply a commercial 2D digital image correlation (DIC) system integrated with a biaxial testing machine to quantitatively characterise the fibrous structure of biological materials. The approach applies a homogeneous biaxial stress field across the tissue and uses optical measurement of the resulting strain field to identify load-bearing collagen architecture. Under this loading condition, collagen bundles deform less than the surrounding matrix, so low-strain bands and their principal directions indicate ligament locations and orientations. The method was validated using an artificial anisotropic material and ex vivo skin, and was then applied to the human hip joint capsule to demonstrate its ability to characterise complex collagen networks. Testing of nine excised hip capsule specimens revealed the collagenous network and the confluence between its fibrous structures. The locations and orientations of seven ligamentous regions were detected and matched to previously published anatomical descriptions. Using strain as a quantitative measure of ligament anatomy further enabled extraction of local mechanical properties, including the tangent modulus, across the entire tissue in a single test. By combining a biaxial testing machine with a commercial 2D DIC system, this study demonstrates a practical and scalable approach for quantifying tissue structure-function relationships across whole tissues.